Coronary intravascular imaging: a piece of history - Abusnina, Waiel; Garcia-Garcia, Hector M.; Rubio, Pablo M.; Mintz, Gary S.; Waksman, Ron (Frontiers in Cardiovascular Medicine, 2025)
Since its early exploration in the 1950s, intracoronary imaging, including intravascular ultrasound (IVUS), optical coherence tomography (OCT), and near-infrared spectroscopy (NIRS), has revolutionized our understanding of coronary artery disease and improved percutaneous coronary intervention outcomes. These technologies have continuously evolved, enhancing our ability to diagnose and treat CAD and ultimately leading to better patient outcomes. This review focuses on the history and key developments of IVUS, OCT, and NIRS.